Localizing Development : Does Participation Work? - Mansuri, Ghazala (Washington, DC: World Bank, 2012)
The Policy Research Report Localizing Development: Does Participation Work? brings analytical rigor to a field that has been the subject of intense debate and advocacy, and billions of dollars in development aid. It briefly reviews the history of participatory development and argues that its two modalities, community-based development and local decentralization, should be treated under the broader unifying umbrella of local development. It suggests that a distinction between organic participation (endogenous efforts by civic activists to bring about change) and induced participation (large-scale efforts to engineer participation at the local level via projects) is key, and focuses on the challenges of inducing participation.